Accidente ofídico causado por Bothrops Asper - Galofre-Ruiz Mario David (Revista Ciencias Biomédicas, 2013)
Introduction: The snake bite of the genus Bothrops is an important cause of ophidic accident in Colombia, with high morbidity and mortality. Clinical case: A case of bite by the snake Bothrops Asper, which was classified as mild grade of poisoning at the entrance of the hospital center is presented. It was managed with antiophidic serum in doses lower than the recommended one, with progression of the symptoms of poisoning. Adjustments in the doses were done and total recovery was reached in five days. Conclusions: Antiophidic serums, named also antivenins, are the cornerstone of the treatment to minimize the local tissue damage and the systemic complications. Rev. cienc.biomed. 2013;4(2):353-357